Pathological and Immunohistochemical Diagnosis of an Intestinal Leiomyosarcoma in a Zebra Finch - Cardoso, João Felipe Rito; Levy, Marcelo Guilherme Bezerra (Brazilian Journal of Veterinary Pathology, 2014)
An adult male Zebra finch (Taeniopygia guttata) with blood in the feces was examined for an internal mass in the abdominal caudal region near to the cloaca. During the necropsy, a large tumor mass around the large intestine was observed. The histopathology was suggestive of smooth muscle tumor and the immunohistochemistry analysis was performed for vimentin, desmin, SMA and KIT for the identification of the tumor histogenesis. The results were consistent with intestinal leiomyosarcoma.